2011
DOI: 10.1093/cercor/bhr268
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity-Based Subdivisions of the Human Right "Temporoparietal Junction Area": Evidence for Different Areas Participating in Different Cortical Networks

Abstract: Controversy surrounds the role of the temporoparietal junction (TPJ) area of the human brain. Although TPJ has been implicated both in reorienting of attention and social cognition, it is still unclear whether these functions have the same neural basis. Indeed, whether TPJ is a precisely identifiable cortical region or a cluster of subregions with separate functions is still a matter of debate. Here, we examined the structural and functional connectivity of TPJ, testing whether TPJ is a unitary area with a het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
473
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 487 publications
(508 citation statements)
references
References 49 publications
31
473
2
2
Order By: Relevance
“…Here, the k-means algorithm started with random assignment and was run 10 times, to find the assignment that minimized the total distance to center. As previous structural connectivity literature has suggested that 3 large-scale networks make connections with the TPJ (Mars et al 2012), the left and right TPJ were initially divided into 3 networks. As these clusters were relatively large, a more fine-grained parcellation was subsequently conducted.…”
Section: Cluster-based Definition Of Tpj Roismentioning
confidence: 99%
See 3 more Smart Citations
“…Here, the k-means algorithm started with random assignment and was run 10 times, to find the assignment that minimized the total distance to center. As previous structural connectivity literature has suggested that 3 large-scale networks make connections with the TPJ (Mars et al 2012), the left and right TPJ were initially divided into 3 networks. As these clusters were relatively large, a more fine-grained parcellation was subsequently conducted.…”
Section: Cluster-based Definition Of Tpj Roismentioning
confidence: 99%
“…As described above, we used 2 clustering analyses: a 3-cluster solution to replicate a prior study of connectivity-based TPJ parcellation (Mars et al 2012), and a more fine-grained 8-cluster solution. Association with decoding measures was examined for both solutions.…”
Section: Tpj Clustering: 8-cluster Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the ASD group, the stepwise regression analyses yielded significant results only for one region: the right angular gyrus / ascending segment of the posterior superior temporal sulcus, also called the temporoparietal junction or TPJ (Corbetta et al 2000;Decety and Lamm 2007;Mars et al 2011). The regression model that could explain gray matter in this region included only performance in the interactivity task as predictor (F(1,9)=13.08, p<0.008; r=.75, r 2 =.56; Figure 3).…”
Section: Social Motion Experimentsmentioning
confidence: 99%